2009
DOI: 10.1063/1.3094918
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the electronic properties of GaxIn1−xP beyond simply varying alloy composition

Abstract: Spontaneous ordering in GaxIn1−xP provides the possibility of tuning electronic structure and improving transport properties. A quasiperiodic twinning structure of two ordered variants offers additional flexibilities in designing the material properties. The superstructure is shown to have distinctively different electronic and electrical properties from the single-variant ordered structure, as revealed in polarized elecroreflectance and cross-sectional scanning Kelvin probe force microscopy measurements. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have provided detailed information on the electronic structures of Ga x In 1−x P alloys (0 ≤ x ≤ 1) [4,5]. The experimental results showed that the luminescence efficiency of Ga x In 1−x P-based LED degrades significantly for emission wavelengths shorter than 590 nm (2.1 eV) [6].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have provided detailed information on the electronic structures of Ga x In 1−x P alloys (0 ≤ x ≤ 1) [4,5]. The experimental results showed that the luminescence efficiency of Ga x In 1−x P-based LED degrades significantly for emission wavelengths shorter than 590 nm (2.1 eV) [6].…”
Section: Introductionmentioning
confidence: 98%
“…Due to the weak luminescence emission, studies on the optical properties of GaxIn1-xP alloys near the direct-indirect band crossover and at the indirect band region are more challenging than studies on direct band alloys. In addition, the lack of latticematched substrates and the ordering effect add more complexity to the studies.Previous studies have provided detailed information on the electronic structures of GaxIn1-xP alloys (0 ≤ x ≤ 1)[81,82]. It was found that the carrier confinement was more difficult for GaxIn1-xP alloys as the Ga content increased[83].…”
mentioning
confidence: 99%